Boosting Jobs and Living Standards in G20 Countries - International Labour Office (World Bank, Washington, DC, 2017)
Almost four years since the onset of the global financial and economic crisis, unemployment and underemployment remain stubbornly high in many G20 countries, and many workers remain trapped in low paid, often informal, jobs with little social protection. Job creation has been anemic in many countries, too slow to fully reabsorb the mass of unemployed and underemployed or, particularly in some emerging market economies, to keep pace with labour force growth and the pressures of rural-urban migration. This raises concerns about the long-term negative effects on human capital, growing inequality and lower future output growth. The political pressures are high, and the risk of a drift towards protectionist measures aimed at 'keeping jobs at home' cannot be ignored. While there is substantial variation in national contexts, G20 countries can help minimize these risks through collective and collaborative work aimed at identifying and implementing credible policy reforms that will boost job creation, employment and the quality of jobs. The report aims at providing a preliminary review of countries' experiences against the backdrop of an evolving economic outlook and could form the basis of a more in-depth analysis, should Ministers request it. Improving labour market outcomes involves several challenges relating to both the quantity and quality aspects of job creation. There is a need in all countries to harness growth to generate labour market opportunities that correspond to labour force growth.